Transcriptome Signatures Predict Phenotypic Variations of Candida auris - Jenull, Sabrina; Tscherner, Michael; Kashko, Nataliya; Shivarathri, Raju; Stoiber, Anton; Chauhan, Manju; Petryshyn, Andriy; Chauhan, Neeraj; Kuchler, Karl (Frontiers in Cellular and Infection Microbiology, 2021)
Health care facilities are facing serious threats by the recently emerging human fungal pathogen Candida auris owing to its pronounced antifungal multidrug resistance and poor diagnostic tools. Distinct C. auris clades evolved seemingly simultaneously at independent geographical locations and display both genetic and phenotypic diversity. Although comparative genomics and phenotypic profiling studies are increasing, we still lack mechanistic knowledge about the C. auris species diversification and clinical heterogeneity. Since gene expression variability impacts phenotypic plasticity, we aimed to characterize transcriptomic signatures of C. auris patient isolates with distinct antifungal susceptibility profiles in this study. First, we employed an antifungal susceptibility screening of clinical C. auris isolates to identify divergent intra-clade responses to antifungal treatments. Interestingly, comparative transcriptional profiling reveals large gene expression differences between clade I isolates and one clade II strain, irrespective of their antifungal susceptibilities. However, comparisons at the clade levels demonstrate that minor changes in gene expression suffice to drive divergent drug responses. Finally, we functionally validate transcriptional signatures reflecting phenotypic divergence of clinical isolates. Thus, our results suggest that large-scale transcriptional profiling allows for predicting phenotypic diversities of patient isolates, which may help choosing suitable antifungal therapies of multidrug-resistant C. auris.